Liberal trade policy and food insecurity across the income distribution: an observational analysis in 132 countries, 2014–17 - Pepita Barlow, DPhil; Rachel Loopstra, PhD; Valerie Tarasuk, ProfPhD; Aaron Reeves, PhD (The Lancet Global Health, 2020)
Summary: Background: Eradicating food insecurity is necessary for achieving global health goals. Liberal trade policies might increase food supplies but how these policies influence individual-level food insecurity remains uncertain. We aimed to assess the association between liberal trade policies and food insecurity at the individual level, and whether this association varies across country-income and household-income groups. Methods: For this observational analysis, we combined individual-level data from the Food and Agricultural Organization of the UN with a country-level trade policy index from the Konjunkturforschungsstelle Swiss Economic Institute. We examined the association between a country's trade policy score and the probability of individuals reporting moderate-severe or severe food insecurity using regression models and algorithmic weighting procedures. We controlled for multiple covariates, including gross domestic product, democratisation level, and population size. Additionally, we examined heterogeneity by country and household income. Results: Our sample comprised 460 102 individuals in 132 countries for the period of 2014–17. Liberal trade policy was not significantly associated with moderate-severe or severe food insecurity after covariate adjustment. However, among households in high-income countries with incomes higher than US$25 430 per person per year (adjusted for purchasing power parity), a unit increase in the trade policy index (more liberal) corresponded to a 0·07% (95% CI −0·10 to −0·04) reduction in the predicted probability of reporting moderate-severe food insecurity. Among households in the lowest income decile (<$450 per person per year) in low-income countries, a unit increase in the trade policy index was associated with a 0·35% (0·06 to 0·60) increase in the predicted probability of reporting moderate-severe food insecurity. Interpretation: The relationship between liberal trade policy and food insecurity varied across countries and households. Liberal trade policy was predominantly associated with lower food insecurity in high-income countries but corresponded to increased food insecurity among the world's poorest households in low-income countries. Funding: Joseph Rowntree Foundation, Economic and Social Research Council.